PAPATEAN: Representational Musical Composition of the Story of the Murder of Missionary A. A. van De Loodstrecht in Bori', Toraja - Saputra, Julian; Picanussa, Branckly; Tika Lestari, Dewi (Universitas Negeri Surabaya, 2024)
The musical composition